Implementation of UNICEF and WHO's care for child development package: Lessons from a global review and key informant interviews - Ahun, Marilyn N.; Aboud, Frances; Wamboldt, Claire; Yousafzai, Aisha K. (Frontiers in Public Health, 2023)
Introduction In the last decade, there has been increased global policy and program momentum to promote early childhood development. The Care for Child Development (CCD) package, developed by UNICEF and the WHO, is a key tool responding to the global demand. The CCD package comprises two age-specific evidence-based recommendations for caregivers to 1) play and communicate and 2) responsively interact with their children (0–5 years) and was designed to be integrated within existing services to strengthen nurturing care for child development. The aim of this report was to provide an up-to-date global review of the implementation and evaluation of the CCD package. Methods In addition to a systematic review of 55 reports, we interviewed 23 key informants (including UNICEF and WHO personnel) to better understand the implementation of CCD. Results The CCD package has been or is being implemented in 54 low- and middle-income countries and territories, and it has been integrated into government services across the health, social, and education sectors in 26 countries. Across these contexts, CCD has been adapted in three primary ways: 1) translations of CCD materials (mostly counseling cards) into local language(s), 2) adaptations of CCD materials for the local context, vulnerable children, or a humanitarian/emergency setting (e.g., including local play activities, using activities that are better suited to children with visual impairments), and 3) substantive modifications to the content of CCD materials (e.g., expansion of play and communication activities, addition of new themes, creation of a structured curriculum). While there is promising evidence and examples of good implementation practice, there has been mixed experience about implementation of CCD with respect to adaptation, training, supervision, integration into existing services, and monitoring implementation fidelity and quality. For example, many users of CCD found difficulties with training the workforce, garnering buy-in from governments, and ensuring benefits for families, among others. Discussion Additional knowledge on how to improve the effectiveness, implementation fidelity and quality, and acceptance of CCD is needed. Based on the findings of the review we make recommendations for future efforts to implement CCD at-scale.